2020
DOI: 10.1007/s40430-020-02588-9
|View full text |Cite
|
Sign up to set email alerts
|

On the machinability of the Ni-30 high-temperature iron-based superalloy

Abstract: Superalloys are high-performance materials which combine high tensile, creep and fatigue strength, besides good ductility, toughness and resistance to corrosion, properties that are also responsible for their low machinability. The VAT 30 ® alloy contains an austenitic stainless steel base with additions of chromium, nickel, titanium and aluminum, and it is mainly applied on the manufacture of valves of combustion engines, due to its advantageous characteristics. This alloy exhibits both high ductility and abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…13 Cutting speed showed no practical consequence on work surface roughness during the performance evaluation of Ni-30 alloy. 14 The results indicated in longitudinal machining of Inconel 601 work specimen and as received coated with TiAlN + AlCr 2 O 3 by PVD tool permits satisfactory flank wear of the tool and needed quality of the machined work piece, while significantly minimizing energy consumption, cutting time, and negative influence on the surroundings. 15 The researchers observed the effect of machining processing factors and cutting tool material on machining forces, surface roughness, and chip compression ratio in turning of super alloys like Inconel 600, Inconel 718, and Inconel 800.…”
Section: Introductionmentioning
confidence: 96%
“…13 Cutting speed showed no practical consequence on work surface roughness during the performance evaluation of Ni-30 alloy. 14 The results indicated in longitudinal machining of Inconel 601 work specimen and as received coated with TiAlN + AlCr 2 O 3 by PVD tool permits satisfactory flank wear of the tool and needed quality of the machined work piece, while significantly minimizing energy consumption, cutting time, and negative influence on the surroundings. 15 The researchers observed the effect of machining processing factors and cutting tool material on machining forces, surface roughness, and chip compression ratio in turning of super alloys like Inconel 600, Inconel 718, and Inconel 800.…”
Section: Introductionmentioning
confidence: 96%
“…It has fine particles with a strengthening γ´ phase when heat treated, giving the superalloy good plasticity and strength. According to AntonialliCarvalho and Diniz (2020), iron-based superalloys cost lower than other superalloys, however, the superalloy lacks most properties that other superalloys possess. Tian et al (2017) reported that the superalloy has poor thermal stability, elevated temperature strength and very hard to machine (Tan et al , 2008).…”
Section: Introductionmentioning
confidence: 99%